Real Exchange Rate Fluctuations and the Dynamics of Retail Trade Industries on the U.S.-Canada Border - Campbell, Jeffrey R; Lapham, Beverly (American Economic Review, 2004)
Real Exchange Rate Fluctuations and the Dynamics of Retail Trade Industries on the U. S.-Canada Border by Jeffrey R. Campbell and Beverly Lapham. Published in volume 94, issue 4, pages 1194-1206 of American Economic Review, September 2004